Disease clearance in ulcerative colitis: Setting the therapeutic goals for future in the treatment of ulcerative colitis - Ramos, Laura; Teo-Loy, Jeny; Barreiro-de Acosta, Manuel (Frontiers in Medicine, 2023)
Ulcerative colitis, one of the phenotypic patterns of inflammatory bowel disease, should be considered a progressive disease with an increased risk of complications if intestinal inflammation is not adequately controlled. The advent of new lines of treatment for this condition has changed and expanded the therapeutic goals to modify its natural history and evolution. The concept of “disease clearance” in ulcerative colitis aims to achieve clinical and biological remission as well as mucosal healing (endoscopic, histological, and in future molecular) in these patients. This review provides the available data on each of the goals of disease clearance in ulcerative colitis to be considered for application in clinical practice in the coming years.